PEMBUATAN PERMEN HERBAL PADA TERNAK KAMBING DI DESA BUKIT SAMANG - Uli Fahrodi, Deka; Marsudi, Marsudi; Sukma Indah, Andi; Saidah Said, Nur; Dunialam Khaliq, Taufik; Putra Ermanda, Adli (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Bukit Samang, is one of the villages in Sendana District, Majene Regency, West Sulawesi. The livestock sector in this village is very developed, especially goat farming. Based on the results of observations in the field, the problem faced by the local community is the lack of veterinary medical personnel in the field, so goat health problems are not quickly resolved, causing farmers to experience losses. There is a lot of potential for plants that can be processed into traditional medicines to treat or prevent disease. The initial stage in mapping partner problems is to carry out a Focus Group Discussion (FGD), which aims to discover the issues Bukit Harapan Farmer Group partners face in Bukit Samang Village. The following are the problems partners face: First, Animal Health Problems. Sudden deaths often occur in goats due to late handling and treatment of sick livestock. Second: HR problems; Farmers' knowledge of plants that have potential as alternative/traditional medicines is still low. The solution offered is education on introducing diseases in goats and plants with potential as conventional medicines and training in making herbal medicines. It also produces new entrepreneurs who can create herbal medicine for livestock labeled